High‐Dielectric Constant Side‐Chain Polymers Show Reduced Non‐Geminate Recombination in Heterojunction Solar Cells. Issue 10 (25th March 2014) - Cho, Namchul; Schlenker, Cody W.; Knesting, Kristina M.; Koelsch, Patrick; Yip, Hin‐Lap; Ginger, David S.; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> High‐dielectric constant side‐chain polymers that show reduced non‐geminate recombination in heterojunction solar cells are reported. Active layer polymers with high dielectric side‐chains show increased performance over alkyl side‐chain polymers. The doubling in efficiency is attributed to suppressed recombination. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>